Antwerp as a production center of paintings (1629-1719) a qualitative and quantitative analysis - Brosens, Koenraad 1947-; Prekel, Inez de (2021)
"Since the 1990s, there has been a steady interest in Antwerp as an early modern production and marketing center of paintings. However, an in-depth view of Antwerp’s supply side in the seventeenth century is still missing. This essay addresses this lacuna by presenting an analysis of the Antwerp Guild of Saint Luke between 1629 and 1719 with a focus on the group of painters. From a methodological point of view, the essay demonstrates that there is great value in a combination of qualitative and quantitative reading of various sources to analyze complex systems, such as artistic communities, and how they evolved through time. In so doing, it illustrates the potential of a slow computational art history approach that maximizes the potential of analysis and exploration of data and data visualizations, while at the same time respecting data contexts and data issues. Our analysis shows that, unsurprisingly, the guild and the community of painters suffered from the economic crisis that hit Antwerp after 1650 and from changes in consumer preferences that occurred in the 1680s. However, the statistics also show that the guild showed remarkable resilience, and that Antwerp remained the prime production center of Flemish painting until 1700. The robustness did not appear out of thin air, but was engineered by the board and established masters. Using the freedom offered by the organizational and regulatory framework, they machinated the number and careers of apprentice painters and founded an Academy in a successful attempt to recruit aspiring artists. This, however, is not to say that established masters favored uncontrolled growth in the cohorts of apprentices, journeymen and masters. Small workshops were and remained the norm. ..."
Keywords: Maler -- 1957-; Geschichte 1629-1719; Malerzunft; Malerei; Antwerpen